A Role for the Non-Canonical Wnt-β-Catenin and TGF-β Signaling Pathways in the Induction of Tolerance during the Establishment of a Salmonella enterica Serovar Enteritidis Persistent Cecal Infection in Chickens - Kogut, Michael H.; Arsenault, Ryan J. (Frontiers in Veterinary Science, 2015)
Non-typhoidal Salmonella enterica induce an early pro-inflammatory response in chickens. However, the response is short-lived, asymptomatic of disease, resulting in a persistent colonization of the ceca, and fecal shedding of bacteria. The underlying mechanisms that control this persistent infection of chickens by Salmonella are unknown. Recently, we found an expansion of the Treg population and subsequent increased in vitro immunosuppressive functions of the CD4+CD25+ cells isolated from the ceca of the Salmonella-infected chickens by day 4 post-infection that increased steadily throughout the course of the 14 days of infection; whereas the number of CD4+CD25+ cells in the non-infected controls remained steady throughout the study. CD4+CD25+ cells from cecal tonsils of S. enteritidis-infected birds had greater expression of IL-10 mRNA content than the CD4+CD25+ cells from the non-infected controls at all the time points studied. These results suggest the development of a tolerogenic immune response in the cecum of Salmonella-infected chickens may lead to the persistance of Salmonella cecal colonization. Using a chicken-specific kinome peptide immune array, we have analyzed the signaling pathways altered during the establishment of this tolerogenic state. This analysis has revealed a role for the non-canonical Wnt signaling pathway in the cecum at 4 days post-infection. Infection induced the significant (p < 0.01) phosphorylation of the G-protein-coupled transmembrane protein, Frizzled 1 (FZD1), which results in an influx of intracellular Ca++ that leads to the activation (phosphorylation) of the Ca++-dependent effector molecules calcium/calmodulin-dependent kinase II (CamKII), β-catenin, protein kinase C (PKC), JUN N-terminal kinase (JNK) and activation of the transcription factor, NFAT. Nuclear translocation of NFAT resulted in a significant increase in the mRNA expression of the anti-inflammatory cytokines IL-10 and TGF-β. Increased expression of TGF-β4